Pengembangan Industri Hijau Pada Industri Kecil Menengah (IKM) Batik Nirmala Sragen - Dora Kusumastuti (Indonesia Berdaya, 2023)
IKM Batik Nirmala is one of the IKMs located in the Masaran Batik center, Batik Nirmala was founded in 2010 with a total of 8 workers who produce an average of 500 pieces of batik each month, both printing, stamping and hand-drawn batik. The problem related to the development of the green industry at Nirmala IKM is how to substitute environmentally friendly raw and auxiliary materials, one of which is by developing natural dyes at Nirmala IKM so that it is expected to be able to reduce the potential for waste generation. The solution to partner problems is the need to use raw materials and auxiliary materials that are safe for the environment, one of which is natural dyes. In this community service activity socialization will be carried out on the use of environmentally friendly raw materials and auxiliary materials